2010
DOI: 10.1136/thx.2009.116756
|View full text |Cite
|
Sign up to set email alerts
|

Continuous positive airway pressure titration for obstructive sleep apnoea: automatic versus manual titration

Abstract: Background and aims Manual laboratory continuous positive airway pressure (CPAP) titration for obstructive sleep apnoea (OSA) is costly, time intensive and delays access to treatment. Automatic positive airway pressure (APAP) titration has the potential to reduce cost and improve access to treatment. The aim of this study was to assess the clinical efficacy and costs of APAP titration compared with manual titration in moderateesevere OSA. Methods Patients with moderateesevere OSA (apnoea/ hypopnoea index >15 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…La estimación aproximada de coste por noche de estudio con titulación manual fue de 817 $, frente a los 647 $ del ajuste con auto-CPAP en el laboratorio, o a los 132 $ para el ajuste de auto-CPAP en domicilio. Un análisis por intención de tratar confirmó la eficacia de la titulación mediante auto-CPAP comparada con la titulación manual 48 .…”
Section: Presión Positiva Continua De La Vía Aérea Métodos De Graduaunclassified
“…La estimación aproximada de coste por noche de estudio con titulación manual fue de 817 $, frente a los 647 $ del ajuste con auto-CPAP en el laboratorio, o a los 132 $ para el ajuste de auto-CPAP en domicilio. Un análisis por intención de tratar confirmó la eficacia de la titulación mediante auto-CPAP comparada con la titulación manual 48 .…”
Section: Presión Positiva Continua De La Vía Aérea Métodos De Graduaunclassified
“…However, auto-CPAP and predicted formula titration could lead to considerable savings and significant reductions in waiting lists. In this respect, MCARDLE et al [85] reported that the total costs for auto-CPAP titration was much lower than those of laboratory auto-CPAP (less than one-third).…”
Section: Costsmentioning
confidence: 99%
“…CPAP is usually set at a pressure sufficient to prevent upper airway collapse in all body positions and sleep stages. CPAP titration is determined by an attended overnight CPAP titration study with full polysomnographic (PSG) monitoring in a sleep laboratory, or by automatic positive airway pressure (APAP) devices [79]. …”
Section: Introductionmentioning
confidence: 99%